Enhancing foam fire suppression analysis through CO2 TDLAS quantification. (January 2022) - Hinnant, Katherine M.; Giles, Spencer L.; Ananth, Ramagopal; Miller, J. Houston
Abstract: Tunable diode laser absorption spectroscopy (TDLAS) was used to monitor CO2 concentrations above a pool fire as experimental firefighting foams were applied to the pool surface. A 2.0 μm diode laser was used in a modified section of ventilation duct above a 19 cm diameter heptane pool fire. Laser signal intensity and temperature were measured to calculate CO2 concentration with time. The concentration profiles were determined for a reference fluorosurfactant foam and a series of fluorine-free foams containing siloxane surfactants blended with a hydrocarbon surfactant (Glucopon 215 UP), and solvent. Seven mixtures were evaluated: three foams fully covered the fuel pool and two foams extinguished the fire. Due to the rapid response of the measurement technique, a dramatic drop in CO2 concentration was observed as the fire was extinguished. Pool coverage corresponded to an observed peak in CO2 concentration. The concentration profiles allowed for a more accurate assessment of foams that were unable to extinguish a pool fire. Further analysis of these profiles may elucidate time-scales important for rapid fire suppression. Defining and characterizing mechanisms of foam fire suppression at these time-scales may improve and accelerate research efforts for the development of fluorine-free surfactants in firefighting foams.